The Recent Topics in Genetic Polymorphisms - Çalışkan, Mahmut; Erol, Osman; Cevahir Öz, Gül (IntechOpen, 2020)
The book in your hands presents chapters revealing the magnitude of genetic polymorphisms that exist in different kinds of living beings. Natural populations contain a considerable amount of genetic change, which provides a genomic flexibility that can be used as a raw material for adaptation to changing environmental conditions. The analysis of genetic polymorphisms provides information about DNA sequence changes at a given locus. The increasing availability of PCR-based molecular markers allows for the detailed analyses and the detection of genetic changes influencing some important traits. The purpose of this book is to provide a glimpse into the dynamic process of genetic polymorphisms by presenting the thoughts of scientists engaged in the generation of new ideas and techniques employed for the assessment of genetic polymorphisms. The book should prove useful to students, researchers and experts in the area of molecular genetics.